2014
DOI: 10.1098/rspb.2013.2570
|View full text |Cite
|
Sign up to set email alerts
|

Population-level effects of suppressing fever

Abstract: Fever is commonly attenuated with antipyretic medication as a means to treat unpleasant symptoms of infectious diseases. We highlight a potentially important negative effect of fever suppression that becomes evident at the population level: reducing fever may increase transmission of associated infections. A higher transmission rate implies that a larger proportion of the population will be infected, so widespread antipyretic drug use is likely to lead to more illness and death than would be expected in a popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 42 publications
0
70
0
1
Order By: Relevance
“…As indicated by Harden et al (9), there is a growing body of evidence to sustain the view that fever is beneficial for the host (15,16). Recently, Earn et al (17) have found that suppression of fever in normal clinical settings can potentially lead to negative effects at the populationlevel, due to a possible increase in the spread of associated infections. Fever is a process in which the body temperature rises, deviating from normal values (7,18), and according to the excellent scientific text of Saladin (18), it is a beneficial process as long as it does not persist, or reaches 44ºC to 46ºC, where it could be fatal or lead to irreversible brain damage.…”
Section: Discussionmentioning
confidence: 96%
“…As indicated by Harden et al (9), there is a growing body of evidence to sustain the view that fever is beneficial for the host (15,16). Recently, Earn et al (17) have found that suppression of fever in normal clinical settings can potentially lead to negative effects at the populationlevel, due to a possible increase in the spread of associated infections. Fever is a process in which the body temperature rises, deviating from normal values (7,18), and according to the excellent scientific text of Saladin (18), it is a beneficial process as long as it does not persist, or reaches 44ºC to 46ºC, where it could be fatal or lead to irreversible brain damage.…”
Section: Discussionmentioning
confidence: 96%
“…Because the death rate is proportional to the rate at which the removed compartment, R, grows, which is proportional to I, the vaccination rate would also be proportional to I. In the electronic supplementary material, appendix E.1.1, we find the final size relations [16][17][18] for the model defined by equation (5.5). These are given by…”
Section: Vaccination Rate / Disease Prevalencementioning
confidence: 99%
“…In group-living animals, the reduction in social interactions may have the further benefit of inhibiting transmission of infection to others within the group, but the difficulties of assessing health in wild animals have hampered studies of sickness behaviour in natural ecological and social contexts. Physiological responses are also important, such as fever; one recent paper took an epidemiological perspective on fever and proposed, via a model and knowledge of how fever reduces viral shedding, that suppression of fever results in higher numbers of influenza cases in human populations [17]. In recent years, our understanding of the mechanisms that underlie sickness behaviours has improved.…”
Section: (C) Sickness Behaviours Affect Sociality and Disease Spreadmentioning
confidence: 99%
“…The specific future directions that we consider involve additional studies of the fitness consequences of parasitism [8]; a greater understanding of behavioural and physiological responses to infectious disease, especially including their effects on individual health and spread of infectious diseases in populations [2,17]; and emerging links between sociality, the microbiome and health.…”
Section: Introductionmentioning
confidence: 99%